Efektivitas Aromatherapy Lemon Balm dan Terapi Musik untuk Mengatasi Ansietas Pasien COVID-19 - Lutfian Lutfian; Ayunda Puteri Rizanti; Ilany Nandia Chandra (Jurnal Berita Ilmu Keperawatan, 2022)
COVID-19 has become a world health issue due to the speed of its spread which is challenging to control. In addition, COVID-19 does not only cause problems in the physical health aspect and has an impact on the patient's psychological health. This situation causes a person who is confirmed to have COVID-19 to experience many psychological disorders such as anxiety; this will affect the immune system and the length of the healing process in patients. The purpose of this article is to determine the effectiveness of lemon balm aromatherapy (Melissa Officinalis) and music therapy in overcoming anxiety in COVID-19 patients in a literature review. The method in writing this article uses a literature review. Articles obtained through search sites: Google Scholar, Science Direct, Scopus, NCBI, and ProQuest. The criteria used in the search are Indonesian and English with a range of publication years 2015-2020. Eight leading journals were used as references in this study; from those journals, it was concluded that lemon balm contains anxiolytic which can improve the state of sleep disorders (insomnia) in clients with anxiety because of COPD, and it was found that music therapy can reduce anxiety in patients who on ventilators. Aromatherapy interventions made from lemon balm and the provision of music therapy are practical efforts to overcome anxiety in COVID-19 patients